MSC-derived exosomes attenuate hepatic fibrosis in primary sclerosing cholangitis through inhibition of Th17 differentiation - Wenyi Chen; Feiyan Lin; Xudong Feng; Qigu Yao; Yingduo Yu; Feiqiong Gao; Jiahang Zhou; Qiaoling Pan; Jian Wu; Jinfeng Yang; Jiong Yu; Hongcui Cao; et al. (Asian Journal of Pharmaceutical Sciences, 2024)
Primary sclerosing cholangitis (PSC) is an autoimmune cholangiopathy characterized by chronic inflammation of the biliary epithelium and periductal fibrosis, with no curative treatment available, and liver transplantation is inevitable for end-stage patients. Human placental mesenchymal stem cell (hpMSC)-derived exosomes have demonstrated the ability to prevent fibrosis, inhibit collagen production and possess immunomodulatory properties in autoimmune liver disease. Here, we prepared hpMSC-derived exosomes (ExoMSC) and further investigated the anti-fibrotic effects and detailed mechanism on PSC based on Mdr2−/− mice and multicellular organoids established from PSC patients. The results showed that ExoMSC ameliorated liver fibrosis in Mdr2−/− mice with significant collagen reduction in the preductal area where Th17 differentiation was inhibited as demonstrated by RNAseq analysis, and the percentage of CD4+IL-17A+T cells was reduced both in ExoMSC-treated Mdr2−/− mice (Mdr2−/−-Exo) in vivo and ExoMSC-treated Th17 differentiation progressed in vitro. Furthermore, ExoMSC improved the hypersecretory phenotype and intercellular interactions in the hepatic Th17 microenvironment by regulating PERK/CHOP signaling as supported by multicellular organoids. Thus, our data demonstrate the anti-fibrosis effect of ExoMSC in PSC disease by inhibiting Th17 differentiation, and ameliorating the Th17-induced microenvironment, indicating the promising potential therapeutic role of ExoMSC in liver fibrosis of PSC or Th17-related diseases.